The influence of quality of work life, perceived union effectiveness and job security on union commitment among bank employees - Nalini, Thamotharan (2018)
This study investigates the influence of quality of work-life, perceived union effectiveness, job security on union commitment among bank employees in Malaysia. This study is motivated by the decline of union density ii worldwide in recent times. Specifically, the objective of the study is to examine the influence of quality of work life, perceived union effectiveness, job security as well as descriptive generational differences and union branch differences on union commitment. To achieve the research objectives, primary data was collected through survey questionnaire which was distributed to all five branches of the National Union ~f Bank Employees (NUBE) in Malaysia. The data were collected from 350 respond end using simple random sampling. The data was analyzed using multiple regression analysis, independent t-test and one-way ANOVA test. The finding of the stuff indicates that quality of work-life, perceived union effectiveness and union brunches had a positive and significant influence on union commitment. On the other hand, job security had shown insignificant influence on union commitment. Thus the representatives or the leaders in NUBE should focus more on the job insecurity of member in banking sector and should not discourage the younger generation to participate in the union activities. Membership declining dilemma can be sort out by giving priorities to important issue such as job security among banking employees.